Peranan Landasan Ilmu Pendidikan dalam Pencegahan Problematika Remaja di Sekolah - Karunia, Marpren; N, Nurfahanah; F, Firman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This artiwl is present to comprehensively study how the foundation of educational science plays an important role in preventing adolescent problematics in school. The discussion will begin with an explanation of the essence and scope of the foundations of educational science, followed by an examination of the various adolescent problems that are rampant in schools, and conclude with an analysis of the concrete role of the educational foundations in the preventive efforts that services can carry out, especially through school counseling. This method was chosen because it corresponds to the main purpose of the article, which is to study, analyze, and expose the foundational role of educational science in the prevention of adolescent problematics in school based on existing theories, concepts, and research results. The results of the study show that educational science foundations have a very important and strategic role in the prevention efforts of adolescent problematics in school. The philosophical aspect provides moral direction and humanistic educational goals, the psychological aspect helps to understand the dynamics of adolescent development, the sociological aspect maps the influence of the social environment, as well as the cultural aspect ensures that prevention efforts are aligned with the cultural values lived in the community. The application of educational science foundations in Guidance and Counseling services makes it a concrete instrument for creating effective and sustainable prevention programs. School counselors, with a deep understanding of educational principles, are capable of designing interventions that are not only reactive, but also proactive in building adolescents’ personal resilience, social skills, and self-awareness.